Fuel characteristics and explosiveness analysis of pulverized coal industrial boilers in China. (January 2020) - Wang, Zhongwei; Zhang, Bing; Qi, Guoli
Abstract: Pulverized coal industrial boilers are widely used in China in recent years for high thermal efficiency and suitable for contract energy management, especially the in service amount is growing fast in regions like Shanxi, Gansu, Shandong, Tianjin, Liaoning, Hebei, etc. Considering the existing operational safety issues of pulverized coal fired industrial boiler, this article researched the relationship between fuel characteristics including calorific value, volatile, ash, moisture and powder explosion in order to explore and analysis in service pulverized coal industrial boilers explosiveness.